Relative Importance Index (RII) of Ethical Leadership Practices Among Academic Staff in Public Higher Learning Institutions in Tanzania - Elias Mseti; Wilfred Lameck; Stella Kinemo (Universitas PGRI Madiun, 2023)
The pinnacle of every country's literacy and the foundation of knowledge creation and management are Higher Learning Institutions (HLIs). Widespread ethical problems are threatening HLIs. Accepting payment or presents in return for grades, utilizing other forms of academic fraud, harassing faculty, staff, and students in a sexual manner both inside and outside of the classroom, abusing power, and plagiarizing are all examples of academic fraud. These moral issues put HLIs in danger and result in the hiring of students who lack the necessary skills. Tanzania's public HLIs were the subject of this study's investigation of ethical leadership practices. The study's target population consisted of 4863 academic staff members at public HLIs in Tanzania. A sample of 350 respondents was drawn from this group using a stratified simple random sampling technique. The input provided by the respondents was examined using the Microsoft Excel application. Relative index analysis was used in this study to order the criteria according to their relative importance. The calculation of the Relative Relevance Index (RII) is important to this study because the outcome shows the ranking level of relevance. It is especially useful for surveys using a Likert scale. The overall findings demonstrate that ethical leadership behaviors in all areas (role clarity, power sharing, integrity, ethical guidance, and fairness) scored Medium-High (M-H), with the highest overall ranking of 0.7 and above. None of the moral behavior received a Higher (0.8) or higher rating. Seven (7) factors received a Medium (0.6) ranking